A randomised, double blind, placebo controlled trial with vitamin D3 as an add on treatment to interferon β-1b in patients with multiple sclerosis. Issue 5 (22nd February 2012) - Soilu-Hänninen, Merja; Åivo, Julia; Lindström, Britt-Marie; Elovaara, Irina; Sumelahti, Marja-Liisa; Färkkilä, Markus; Tienari, Pentti; Atula, Sari; Sarasoja, Taneli; Herrala, Lauri; Keskinarkaus, Irma; Kruger, Johanna; et al.
Abstract : Objectives: To study the safety and efficacy of vitamin D3 as an add on therapy to interferon β-1b (IFNB) in patients with multiple sclerosis (MS). Methods: 1 year, double blind, placebo controlled, randomised study in 66 MS patients. The primary outcomes were T2 burden of disease (BOD) on MRI scans, proportion of patients with serum levels of 25-hydroxyvitamin D (25(OH)D) ≥85 nmol/l or intact parathyroid hormone (PTH) ≤20 ng/l, and number of adverse events. Secondary outcomes were number of MRI enhancing T1 lesions and new T2 lesions, annual relapse rate, changes in the Expanded Disability Status Scale score, timed 25 foot walk test and timed 10 foot tandem walk tests. Results: Median change in BOD was 287 mm 3 in the placebo group and 83 mm 3 in the vitamin D group (p=0.105). Serum levels of 25(OH)D increased from a mean of 54 (range 19–82) nmol/l to 110 (range 67–163) nmol/l in the vitamin D group. 84% of patients reached a serum 25(OH)D level >85 nmol/l in the vitamin D group and 3% in the placebo group (p<0.0001). Patients in the vitamin D group showed fewer new T2 lesions (p=0.286) and a significantly lower number of T1 enhancing lesions (p=0.004), as well as a tendency to reduced disability accumulation (p=0.071) and to improved timed tandem walk (p=0.076). There were no significant differences in adverse events or in the annual relapse rate. Conclusion: Vitamin D3 add on treatment to IFNB reduces MRI disease activity in MS. Trial registration number: EudraCT number 2007-001958-99 and ClinicalTrialsGov number NCT01339676 .